AB0634 Rituximab in systemic sclerosis-interstitial lung disease, a case series of 18 patients. (15th June 2017) - Guzelant, G; Melikoglu, M; Musellim, B; Yilmaz, DD; Fresko, I; Seyahi, E; Hatemi, G; Ugurlu, S; Hamuryudan, V
Abstract : Background: Interstitial lung disease (ILD) is a severe complication of systemic sclerosis (SSc). Immunosuppressives such as cyclophosphamide (CYC) and mycophenolate mophetil (MMF) are used in its treatment with no proven efficacy (1). Rituximab (RTX) appears to be an emerging agent according to case series. Objectives: This retrospective study aims to evaluate the efficacy of RTX on SSc-ILD in a group of patients followed in our center. Methods: A chart review revealed 18 patients (16 women, 2 men; mean age 50.3±12.1 SD years (range 30–72), mean disease duration 8.3±9.3 SD years) with SSc who have been diagnosed as having ILD (confirmed by high-resolution thorax computed tomography and pulmonary function tests) and have been treated with one or more cycles of RTX. Efficacy was evaluated according to the criteria of the American Thoracic Society: improvement= an increase in FVC≥10% or DLCO≥15%; worsening= a decrease in FVC≥10% or DLCO≥15%; stabilization= changes in FVC less than 10% or DLCO less then 15% (2). Results: Four patients were treatment naive for ILD when they received RTX (Group 1). The mean duration between the diagnosis of ILD and RTX treatment in Group 1 was 3.5 months (range 0–14 months). The average RTX cycle in this group was 2 with 1 patient also receiving mycophenolate mophetil in combination with RTX. The mean follow-up time after the initiation of RTX in this group was 12.2±6.8 SD months (range 7–22 months). FVC/DLCO was stable or improved in 2/4 compared to baseline and worsened in 2/4 at the end of follow-up at group 1. Fourteen patients had a 10.2 years-history of SSc and have been treated with immunosuppressives (cyclophosphamide, azathioprine, methotrexate, MMF) for ILD before RTX (Group 2). The mean duration between the diagnosis of ILD and RTX treatment in Group 2 was 71.2 months (range 5–246 months). These patients received a mean of 3 cycles of RTX with 5 receiving MMF (n=3) or AZA (n=2) in addition to RTX. One patient died after 3 months following the first RTX cycle (unknown reason) and 1 was unsuitable for spirometry because of microstomia. Of the remaining 12 patients in Group 2, improvement or stabilisation was seen in 7 and worsening was seen in the remaining 5 patients. Conclusions: RTX appears to be modestly effective for ILD of SSc. The duration of ILD as well as the presence or absence of previous immunosuppressive therapy do not appear as playing a role in response. References: Avouac J et al. EULAR Scleroderma Trials and Research group (EUSTAR) recommendations for the treatment of systemic sclerosis. Ann Rheum Dis 2009. An Official ATS/ERS/JRS/ALAT Statement: IPF: Evidence-based Guidelines for Diagnosis and Management. Disclosure of Interest: None declared